Unraveling the Link between Obesity and Tuberculosis: A Systematic Review of the Underlying Mechanisms - Deddy Herman; Rizanda Machmud; Nur Indrawaty Lipoeto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Tuberculosis (TB) and obesity are significant global health concerns with potentially complex interactions. Obesity, through its effects on metabolism, inflammation, and the immune system, may influence TB susceptibility, progression, and treatment outcomes. This systematic review aims to analyze the published literature on the relationship between obesity and TB, focusing on the underlying mechanisms. Methods: A systematic search of PubMed, Science Direct, and Google Scholar was conducted for articles published in the last 10 years. The search strategy included keywords such as "tuberculosis," "TB," "obesity," and "BMI." Articles were selected using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. Results: The review identified 11 studies that met the inclusion criteria. The studies revealed a complex relationship between obesity and TB, with nutritional status, immunity, and diabetes mellitus (DM) playing key roles. Obesity can alter the immune response to TB, potentially increasing the risk of disease and affecting treatment efficacy. Conclusion: The relationship between obesity and TB is multifaceted, with obesity potentially influencing both disease susceptibility and outcomes. Further research is needed to fully elucidate the underlying mechanisms and to develop targeted interventions for individuals with both obesity and TB.